The concept of belonging: Critical, normative and multicultural. (October 2019) - Chin, Clayton
Contemporary diversity politics is mobilized around debates on the effects of diversity on political community and cohesion. However, social and political theory are deeply divided on the relation between that diversity, liberal–democratic citizenship, multiculturalism and social cohesion. This article argues that a focus on the concept of belonging, which is often employed but rarely examined in detail, illustrates the critical–normative divide between social and political theory. Further, it argues that each has a partial account of belonging that fails to account for the multidimensional and complex nature of diverse belonging today. Instead, it sketches a theory of 'multicultural-belonging', which unites the critical and normative approaches and offers key insights going forward in the analysis of diversity, citizenship and multiculturalism.